PENANAMAN NILAI TAT TWAM ASI PADA ANAK USIA DINI MELALUI KEGIATAN BERMAIN BERSAMA DI PAUD WIDYA DHARMA BONDALEM - Kadek Anggarini; Komang Trisna Mahartini; Komang Agus Budhi Arya Pramana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of instilling character values in early childhood through activities that are appropriate to their developmental stage. At PAUD Widya Dharma Bondalem, several children were still found to exhibit egocentric behavior, reluctance to share, emotional outbursts during play, and limited ability to appreciate their peers' feelings. This study aimed to analyze teachers' strategies for instilling the values of Tat Twam Asi through collaborative play activities, identify the supporting and inhibiting factors in its implementation, and examine its implications for the social behavior development of early childhood learners. The study employed a descriptive qualitative approach conducted at PAUD Widya Dharma Bondalem. Data were collected through observation, in-depth interviews, and documentation using triangulation techniques. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data collection, data condensation, data display, and conclusion drawing. The findings revealed that teachers implemented the values of Tat Twam Asi through role modeling, group play, the habituation of sharing and helping behaviors, and role-playing activities integrated into collaborative play. Supporting factors included teachers' exemplary behavior, a conducive school environment, parental support, local cultural values, and cooperative play activities. Meanwhile, the inhibiting factors consisted of differences in children's characteristics, inconsistent character reinforcement at home, excessive gadget use, limited instructional time, and conflicts among children during play. Collaborative play activities were found to have positive implications for children's social behavior by enhancing empathy, mutual respect, cooperation, social awareness, and children's understanding of the importance of living harmoniously in accordance with the values of Tat Twam Asi.